Crystal-chemical controls on the partitioning of Sr and Ba between plagioclase feldspar, silicate melts, and hydrothermal solutions - Blundy, J; Wood, B (1991)
The isothermal (750°C) experiments of Lagache and Dujon (1987) reveal that the partitioning of Sr between plagioclase feldspar and hydrothermal solutions is a funtion of the anorthite (An) content of the plagioclase, indicating that crystal chemistry may exert a powerful influence on trace element partitioning. In order to compare these results with those on trace element partitioning between plagioclase and silicate melts we have compiled from the literature a large dataset of experimental and volcanic distribution coefficients (D's) for Sr (and Ba). These data, which span a compositional range from lunar basalt to high silica rhyolite and a temperature range of over 650°C, show a relationship between DSr (and DBa) and mole fraction An (XAn) which is similar to that exhibited by the hydrothermal results obtained at constant temperature. Plots of In DSr and In DBa versus XAn are linear with negative slope, indicating that both elements are more compatible in albite than anorthite. In terms of molar distribution coefficients (DSr*) the hydrothermal and silicate melt data display an identical linear relationship between RT In DSr* (where T is the absolute temperature in K and R is the gas constant, 8.314 JK-1 mol-1) and XAn. We conclude therefore that crystal chemistry provides the dominant control on partitioning of Sr and Ba into plagioclase and that the effects of temperature, pressure, and fluid composition are minor. Apparent relationships between DSr (and DBa) and the reciprocal temperature (1/T) are artefacts of the linear relationships between XAn and 1/T in the experimental studies. By defining a Henry's law standard state for the silicate melts and hydrothermal solutions, and considering plagioclases to be ternary regular solutions, we are able to relate the observed relationships between RT In Di* (where i is Ba or Sr) and XAn to the excess free energies of the trace element partitioning reactions between plagioclase and melt or hydrothermal solution. The interaction parameters are consistent with simple models in which the larger Ba or Sr cations are accommodated by lattice strain in the host plagioclase lattice, which is assumed to be perfectly elastic and isotropic. Thus Di* is a function of the Young's modulus of the host crystal and the size mismatch between trace and host cations. The greater elasticity of albite relative to anorthite accounts for the observed preference of Sr and Ba for sodic plagioclases over calcic plagioclases. For geochemical purposes the weight fraction partition coefficient Di is of more value than its molar counterpart. Regression of the Di data versus XAn yields the semi-empirical relationships RTIn DSr = 26,800 - 26,700 · XAnRTIn DBa = 10,200 - 38,200 · XAn. Thus measurement of the An and trace element (Ba, Sr) contents of a magmatic plagioclase enables calculation of the Ba and Sr contents of the coexisting liquid, which can be extremely important in the deciphering of igneous processes. By reference to plagioclase fractionation in the simple An-Ab binary we show that failure to take into account the compositional dependence of DSr can result in erroneous interpretations of geochemical trends. We also consider applications to three natural igneous suites: the Aden Volcanics; the layered Kiglapait Intrusion, Labrador; and the southern Actamello Massif, Italy. © 1991.